PENURUNAN FONDASI TIANG TUNGGAL PADA PEMBEBANAN LATERAL AKIBAT PENAMBAHAN BEBAN AKSIAL - Aziz Abdul Majid; Bambang Setiawan; Niken Silmi Surjandari (Jurnal Riset Rekayasa Sipil, 2025)
The pile foundation is the lower building structure that supports the above structure. Pile foundations withstand combined loads from the vertical and horizontal directions. In the field, both loads work simultaneously. However, in Indonesia, in general, the axial and lateral loading tests are carried out separately. Related to this, there have been few investigations on the influence of combined loads on pile foundations. These led to inconsistent results to the effects of adding the axial load on the lateral loading. The three-dimensional finite element method is used in this study to analyze the effect of vertical displacement on a single pile foundation with the additional axial loads on lateral loads. Two pile foundation models were made, the first pile foundation model is a single pile foundation without a pile cap, while the second pile foundation model is modeled with a pile cap. Two models were applied by the lateral load with the additional variation axial load of 0H, 0.25H, 0.5H, 0.75H, and 1H. The vertical displacement is significantly decreased in the pile foundation model with a pile cap compared to the pile foundation model without a pile cap. The reduction in vertical displacement of pile foundations with a pile cap due to the addition of axial loads affects up to 30%, 24%, 19%, 16%, 14% of pile foundations without a pile cap, respectively. This research is expected to help decision making consideration in the design and planning for pile foundations.